Trichophyton equinum infections among young wrestlers in Hungary - Erös, N... (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 1999)
Epidemic-like tinea corporis and capitis cases were seen among a group of wrestlers aged from 8 to 17 years in Miskolc (Hungary) between July of 1997 and August of 1998. The fungal cultures revealed Trichophyton equinum as causative agent. Anthropophilic spreading of this zoophilic dermatophyte couldbe stemmed by using topical and systemic antimycotics and with special preventive measures.
Keywords: Diagnosis; Epidemiology; Tinea; Trichophytin; Wrestling